Analisis dan Perancangan U-Slot Patch Single Layer Microstrip Antenna 2,4 GHz pada Teknologi Zigbee - Marini, Sri; Asrika, Sukwati Dewi; Handayani, Dwipa; Mhammadin, Habib (JREC (Journal of Electrical and Electronics), 2020)
The antenna is the most important part in a wireless communication system. Microstrip one type of antenna that has practical size and dimensions that are simple and easy to fabricate. In this research, we designed and analyzed two slit single layer microstrip antennas for Zigbee technology applications that operate in the 2.4 GHz band. Today, this application has become important for everyday use in industry and home automation, in small areas due to low power requirements for operation and long battery life. The antenna is built on FR-4 epoxy substrate with a thickness of 1.6 mm and Îµr = 4.4. Antennas operating at 2.4 GHz Resonance frequency have a VSWR value of 1.8 and a Returnloss value of -11 dB with a Vertical radiation pattern, resulting in a narrow impedance bandwidth that can protect the Antenna against interference from other applications in the ISM band. The antenna produced has a patch size of 5.2 cm Ã— 5.2 cm2 with a slit distance of 1 mm. Antennas have advantages in simple design, narrow bandwidth, and their compact size and ease of publication, the test results of the parameters-Parameters, the antenna has met the qualifications of a good antenna standard for zigbee technology.